2000
DOI: 10.2746/042516400777591633
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of right ventricular function in the exercising horse: use of the Fourier Transform

Abstract: Summary The objective of this study was to develop and test a technique to allow dynamic cardiac function to be studied during exercise in the horse. Blood pressure waveforms in the exercising horse are difficult to interpret because of the large influence of stride and respiration. A method has been devised to study dynamic right ventricular variables during high‐speed exercise in the horse. A Fast Fourier Transform was performed on the digitised pressure waveforms and the frequency components associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…For the test, each horse galloped at 110% of the speed necessary to elicit VO 2max for 2 min. Analogue RV pressure signals were filtered with a low-pass filter set at 100 Hz and digitised at a sampling rate of 500 Hz, as described in Weigle et al (2000). Signals were recorded continuously on a computerbased data acquisition system 8 .…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…For the test, each horse galloped at 110% of the speed necessary to elicit VO 2max for 2 min. Analogue RV pressure signals were filtered with a low-pass filter set at 100 Hz and digitised at a sampling rate of 500 Hz, as described in Weigle et al (2000). Signals were recorded continuously on a computerbased data acquisition system 8 .…”
Section: Experimental Protocolmentioning
confidence: 99%
“…A number of sensitive indicators of ventricular function have been proposed. The maximal rate that ventricular pressure is developed (dP/dtmax), the maximal rate of ventricular relaxation (dP/dtmin), the time constant for ventricular relaxation (tau), and maximal and minimal ventricular pressures have all been used to describe ventricular function in horses Grubb et al 1999;Weigle et al 2000). Additionally, several authors have reported the use of right ventricular dP/dtmax to evaluate myocardial function in resting or submaximally exercising horses (Wagner et al 1991;Hinchcliff et al 1995;Grubb et al 1996;Nollet et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximal HR was determined from the pulmonary arterial pressure waveform. Pulmonary arterial pressure waveforms were Fourier transformed to allow independent analysis of the underlying cardiac, respiratory and stride frequencies (Weigle et al 2000). At maximal exercise, the peak around 2 Hz is associated with respiratory and stride frequency and the peak around 4 Hz is the cardiac frequency.…”
Section: Cardiac Output and Stroke Volumementioning
confidence: 99%
“…Also, the observation of physiological adaptations to the systematic exercise is an important tool in evaluating the sportive performance of athlete horse (Baldissera, 1997). The heart rate influences physiologic alterations that occurs before and after the exercise and the speed of its return depends on the exercise intensity and duration, the animal conditioning and the environmental conditions (Weigle et al, 2000).…”
Section: Introductionmentioning
confidence: 99%